Akuntansi Al Istishna - Alfio Surya Renaldi; M.Firly; Nala Ratih (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Istishna' is one of the muamalat contracts used in sharia banking products which includes sharia bank fund distribution or financing products with the principle of buying and selling. The istishna' operational mechanism in sharia banks is carried out in accordance with existing sharia regulations. The general characteristics of the ordered goods must be known, including type, technical specifications, quality and quantity. The ordered goods must comply with the characteristics agreed upon between the seller and the manufacturer/seller. If the ordered goods are sent incorrectly or are defective, the producer/seller must be responsible for their negligence. Therefore, the accounting treatment if the settlement of Istishna receivables is carried out by prepayment, then the accounting treatment follows the accounting treatment for Salam transactions, but the term